The Short- and Long-Term Effects of a Short Course of Sauerkraut Supplementation on the Gut Microbiota of Active Athletes: A Pilot Follow-Up Study - Zonjić, Jadran; Karačić, Andrija; Brodić, Ivona; Starčević, Antonio; Renko, Ira; Krznarić, Željko; Ivančić, Matija; Liberati Pršo, Ana-Marija; Šatalić, Zvonimir (Nutrients, 2025)
Objectives: The application of whole fermented foods in sports nutrition for gut microbiota personalization is a promising area of investigation. Sauerkraut, a traditional fermented food, has not been extensively studied in this context. This study aimed to replicate earlier findings of a proof-of-concept study on the potential of sauerkraut for gut microbiota personalization in active athletes. Methods: A pilot follow-up study was conducted on active recreational athletes who consumed 250 g of organic pasteurized sauerkraut daily for 10 days. Changes in gut microbiota composition and functionality were assessed using 16S rRNA sequencing and metabolic pathway analysis across three time points: pre-intervention, postintervention, and one-month postintervention. Laboratory parameters, bowel function, and side effects were monitored throughout the study. Results: In total, 11 male participants with an average age of 30 years completed the study. The pilot follow-up study did not replicate the original study’s findings on sauerkraut’s short-term effects on β-diversity and taxonomic and functional groups. However, long-term effects of sauerkraut supplementation were demonstrated, including a significant reduction in α-diversity variance and increased gut microbiota composition similarity (β-diversity) as well as several significant changes in bacterial taxa and metabolic pathways after a washout period. The intervention also induced a transient decrease in B12 vitamin levels and a short- and long-term increase in leukocyte concentrations. The probability for physiological types of stools increased after one week of sauerkraut supplementation as well as the incidence of gastrointestinal side effects, such as bloating, diarrhea, pain, nausea, and constipation. Conclusions: This study suggests that the short-term effects on the gut microbiota of sauerkraut supplementation depend on its baseline status, but it can induce long-term effects. Sauerkraut supplementation requires a seven-day adaptation period. Further research is needed to explore the mechanisms behind the short- and long-term effects of sauerkraut supplementation.